The influence of company size, company age, profitability, leverage, sales growth, and independent board of commissioners on Islamic social reporting disclosures - Vika Fitranita; Duta Widiyaksa; Baihaq; Dri Asmawanti (Proceeding International Conference on Accounting and Finance, 2023)
This study aims to provide empirical evidence on the effect of firm size, firm age, profitability, leverage, sales growth, and an independent board of commissioners on disclosure of Islamic social financial reporting. This study was tested using multiple regression analysis. The sample used in this study is a manufacturing company listed on the Indonesian Sharia Stock Index (ISSI) for 2018-2020. The sample in this study was selected using a purposive sampling method with a total sample of 204 observations. The results showed that company size had a positive effect on the disclosure of firm age, leverage, and sales growth and independent commissioners had no effect on the disclosure of Islamic Social Reporting.